2018
DOI: 10.1186/s12871-018-0493-9
|View full text |Cite
|
Sign up to set email alerts
|

Visual quality assessment of the liver graft by the transplanting surgeon predicts postreperfusion syndrome after liver transplantation: a retrospective cohort study

Abstract: BackgroundThe discrepancy between demand and supply for liver transplants (LT) has led to an increased transplantation of organs from extended criteria donors (ECD).MethodsIn this single center retrospective analysis of 122 cadaveric LT recipients, we investigated predictors of postreperfusion syndrome (PRS) including transplant liver quality categorized by both histological assessment of steatosis and subjective visual assessment by the transplanting surgeon using multivariable regression analysis. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 38 publications
2
34
0
Order By: Relevance
“…Similar to previous studies, higher rates of PRS, as seen in our microsteatosis group, resulted in a more complicated postoperative course. (23) Patients in the microsteatosis group had higher rates of EAD (38.2%) than patients in the no steatosis group (23.0%). Four previous studies reported the rates of delayed graft function (DGF)/ EAD in patients receiving a liver graft with microsteatosis compared with liver grafts with little or no steatosis.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Similar to previous studies, higher rates of PRS, as seen in our microsteatosis group, resulted in a more complicated postoperative course. (23) Patients in the microsteatosis group had higher rates of EAD (38.2%) than patients in the no steatosis group (23.0%). Four previous studies reported the rates of delayed graft function (DGF)/ EAD in patients receiving a liver graft with microsteatosis compared with liver grafts with little or no steatosis.…”
Section: Discussionmentioning
confidence: 86%
“…PRS was seen in a larger proportion of patients receiving donor livers with microsteatosis ≥30% (33.1%) than in the matched cohort of patients receiving livers with no steatosis (24.2%). Similar to previous studies, higher rates of PRS, as seen in our microsteatosis group, resulted in a more complicated postoperative course . Patients in the microsteatosis group had higher rates of EAD (38.2%) than patients in the no steatosis group (23.0%).…”
Section: Discussionmentioning
confidence: 97%
“…Six studies were conducted in China [ 17 , 18 , 27 , 30 ], two each in Republic of Korea [ 8 ] and Japan [ 25 ], and United States [ 9 , 24 , 33 , 34 ], one each in Turkey [ 29 ], Switzerland [ 26 ], Italy [ 7 ], and Spain [ 28 ]. Most of the studies were cross-sectional studies except two cohort studies [ 7 , 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies were conducted in China [18,19,28,31], two each in Republic of Korea [8] and Japan [26], and United States [9,25,34,35], one each in Turkey [30], Switzerland [27], Italy [7], and Spain [29].…”
Section: Study Characteristicsmentioning
confidence: 99%